2021
DOI: 10.3389/fpubh.2021.678346
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Weight Status of Primary School Children in Serbia

Abstract: The purpose of the present cross-sectional study was to examine dietary patterns and the prevalence of underweight, overweight, and obesity among Serbian children. Furthermore, the study analyzed the association between dietary patterns and weight status. A nationally representative sample of 6–9-year-old children (n = 3,067) was evaluated as part of the Fifth Round World Health Organization European Childhood Obesity Surveillance Initiative. The children's height and weight were measured by trained field exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Fifteen observational studies ( 12 , 32 , 34 , 35 , 38 , 39 , 41 , 44 , 45 , 47 , 49 , 52 , 53 , 57 , 64 ) showed that skipping breakfast was positively associated with overweight in children and adolescents (OR, 1.37; 95% CI , 1.23–1.54; P < 0.001; Figure 2 ). Nine studies ( 32 , 38 , 39 , 47 , 49 , 57 , 63 , 64 , 66 ) illustrated that skipping breakfast was positively associated with obesity in children and adolescents (OR, 1.51; 95% CI , 1.30–1.76; P < 0.001; Figure 3 ). Four articles ( 43 , 45 , 54 , 58 ) provided data on the effect of skipping breakfast on overweight or obesity in children and adolescents (OR, 1.59; 95% CI , 1.33–1.90; P < 0.001; Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen observational studies ( 12 , 32 , 34 , 35 , 38 , 39 , 41 , 44 , 45 , 47 , 49 , 52 , 53 , 57 , 64 ) showed that skipping breakfast was positively associated with overweight in children and adolescents (OR, 1.37; 95% CI , 1.23–1.54; P < 0.001; Figure 2 ). Nine studies ( 32 , 38 , 39 , 47 , 49 , 57 , 63 , 64 , 66 ) illustrated that skipping breakfast was positively associated with obesity in children and adolescents (OR, 1.51; 95% CI , 1.30–1.76; P < 0.001; Figure 3 ). Four articles ( 43 , 45 , 54 , 58 ) provided data on the effect of skipping breakfast on overweight or obesity in children and adolescents (OR, 1.59; 95% CI , 1.33–1.90; P < 0.001; Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen observational studies (12,32,34,35,38,39,41,44,45,47,49,52,53,57,64) showed that skipping breakfast was positively associated with overweight in children and adolescents (OR, 1.37; 95% CI, 1.23-1.54; P < 0.001; Figure 2). Nine studies (32, 38, 39, 47, 49, 57, 63, 64, 66) illustrated that skipping breakfast was positively associated with obesity in children and adolescents (OR, 1.51; 95% CI, 1.30-1.76; P < 0.001; Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study [26] determined the overall prevalence of overweight (23.1%, including obesity) in Serbian primary school children, which was comparable to the relatively high rates reported in some other European countries. Even these results indicated the epidemic of obesity in Serbian children [27]; however, the results of a more recent cross-sectional study [27] were even worse regarding the percentage of obesity in children. In a nationally representative sample containing 3067 6-9-year-old children, the overall prevalence of overweight (including obesity) was 28.9%.…”
Section: Public Policies In Serbiamentioning
confidence: 87%
“…Therefore, a significant public health target would be to lower sugar intake in children's diets (and, in particular, in the diet of young athletes). Taking into account the information on the habits of using sugar in the diet and the percentage of overweight children [27], it is necessary to regulate interventions and activities that would reduce sugar intake from early childhood. In this sense, synchronizing public health and education policies could have positive effects.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%